2020
DOI: 10.1073/pnas.2004524117
|View full text |Cite
|
Sign up to set email alerts
|

Social bonds do not mediate the relationship between early adversity and adult glucocorticoids in wild baboons

Abstract: In humans and other animals, harsh conditions in early life can have profound effects on adult physiology, including the stress response. This relationship may be mediated by a lack of supportive relationships in adulthood. That is, early life adversity may inhibit the formation of supportive social ties, and weak social support is itself often linked to dysregulated stress responses. Here, we use prospective, longitudinal data from wild baboons in Kenya to test the links between early adversity, adult social … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
85
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(90 citation statements)
references
References 88 publications
(131 reference statements)
5
85
0
Order By: Relevance
“…Other social gradients, including social integration and early-life adversity, are robustly linked to survival in both humans and nonhuman animals ( 50 ), including this baboon population ( 37 , 38 ). Recent work with the Amboseli baboons has shown that weak social bonds in adulthood do play a mediating role in pathways that may connect conditions experienced in early life with adult GC levels ( 51 ). A priority for future work should be to examine causal relationships between GCs and social gradients to understand the pathways through which they are linked to survival.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other social gradients, including social integration and early-life adversity, are robustly linked to survival in both humans and nonhuman animals ( 50 ), including this baboon population ( 37 , 38 ). Recent work with the Amboseli baboons has shown that weak social bonds in adulthood do play a mediating role in pathways that may connect conditions experienced in early life with adult GC levels ( 51 ). A priority for future work should be to examine causal relationships between GCs and social gradients to understand the pathways through which they are linked to survival.…”
Section: Resultsmentioning
confidence: 99%
“…Because there is interannual variation in the intensity and duration of the wet and dry seasons, we also calculated a 3-month rainfall anomaly as the difference between the total rainfall in the 3 months preceding sample collection and the long-term average for the same calendar dates based on the entire 43-year rainfall record. We followed the procedure used in ( 51 ) to account for within-season rainfall variability on fGC concentrations. We calculated the mean of daily maximum temperature in the 30 days before and including the day of sample collection because previous research has shown that, within seasons, fGC concentrations are elevated during months with relatively high daily maximum temperatures ( 29 ).…”
Section: Methodsmentioning
confidence: 99%
“…While the effect of maternal loss on wild animal survival and reproduction has been recently established ( Foster et al, 2012 ; Andres et al, 2013 ; Tung et al, 2016 ; Walker et al, 2018 ; Surbeck et al, 2019 ; Crockford et al, 2020 ; Zipple et al, 2021 ), the mechanisms underlying these fitness costs remain understudied. Our study provides one of the rare empirical tests of the BEM (see also Rosenbaum et al, 2020 ) and ACM in wild long-lived mammals by assessing the short- and long-term physiological impacts of early maternal loss. While we found an effect of maternal loss on diurnal cortisol slopes in immature chimpanzees whose mothers died recently ( all immature and immature orphan models ), these effects were neither present in individuals who lost their mothers more than 2 years earlier ( all immature and immature orphan models ) nor in mature male chimpanzees ( adult male orphan model ).…”
Section: Discussionmentioning
confidence: 99%
“…A study on wild female baboons, using extensive long-term data, showed that simultaneous exposure to several forms of early-life adversity, and some isolated forms of adversity such as drought and low maternal rank, leads to an overall elevation in glucocorticoid levels in adulthood ( Rosenbaum et al, 2020 ), offering support for the BEM. However, maternal loss in isolation did not lead to long-term elevation of glucocorticoid levels, suggesting that baboons may have buffering mechanisms to offset the effects of biological embedding for some forms of early-life adversity.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Shah demonstrated that this pattern is driven by reproductive tradeoffs between different tactics that might not have been evident from a cross‐sectional study. Finally, Elizabeth Archie and Elizabeth Lange described work in yellow baboons ( Papio cynocephalus ) that used long‐term data to link negative early life conditions to endocrine dysfunction, reduced adult social bonds, and decreased lifespan 9–11 . Their work illustrates the long‐lasting effects of early life environments and how early life and adult phenotypes drive health differences among individuals.…”
Section: Speaker Institution Title Linkmentioning
confidence: 99%